2006
DOI: 10.1186/cc4927
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: IntroductionThis paper describes the case mix, outcome and activity for admissions to intensive care units (ICUs) with community-acquired pneumonia (CAP).MethodsWe conducted a secondary analysis of a high quality clinical database, the Intensive Care National Audit & Research Centre (ICNARC) Case Mix Programme Database, of 301,871 admissions to 172 adult ICUs across England, Wales and Northern Ireland, 1995 to 2004. Cases of CAP were identified from pneumonia admissions excluding nosocomial pneumonias and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(44 citation statements)
references
References 21 publications
2
38
0
4
Order By: Relevance
“…[79,80] One early study suggested that admission to the ICU did not improve patient outcomes, though it had methodological limitations, as patients were only admitted to the ICU late in their course, perhaps too late to derive much benefit from intensive therapy. [81] One recent study showed that patients with CAP requiring vasopressor therapy in the ED who were admitted to the ICU had lower mortality than those admitted to the floor, though this could reflect unstated or unrecorded requests to limit care, as it seems unusual to admit a patient with vasopressor dependence to the hospital ward.…”
Section: E Implications Of Severity Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[79,80] One early study suggested that admission to the ICU did not improve patient outcomes, though it had methodological limitations, as patients were only admitted to the ICU late in their course, perhaps too late to derive much benefit from intensive therapy. [81] One recent study showed that patients with CAP requiring vasopressor therapy in the ED who were admitted to the ICU had lower mortality than those admitted to the floor, though this could reflect unstated or unrecorded requests to limit care, as it seems unusual to admit a patient with vasopressor dependence to the hospital ward.…”
Section: E Implications Of Severity Assessmentmentioning
confidence: 99%
“…[54] A study of a large British cohort suggested worse outcome for late ICU admissions but did not control for disease severity. [80] Our preliminary data[82] and a recent post hoc analysis of multi-center prospective observational studies[83] suggest that initial ICU triage may be associated with better outcomes, though neither analysis has yet controlled for rapidly progressive pneumonia, a crucial confounder of the proposed relationship between ICU triage and mortality. [84]…”
Section: E Implications Of Severity Assessmentmentioning
confidence: 99%
“…Up to 10% of hospitalized adult CAP patients require intensive medical care and are transferred to intensive care units (ICUs) [5] with great impact on health care costs [3,6] and outcome. Mortality of sCAP patients admitted to ICUs usually ranges from 35 to 58% depending on time and admission to hospital [7]. However, two recent trials on sCAP found a mortality rate of only 17.9% [ 8] and 23.1% [9].…”
Section: Introductionmentioning
confidence: 99%
“…102, 103 One early study suggested that admission to the ICU did not improve patient outcomes. However, it had methodological limitations as patients were only admitted to the ICU late in their course, perhaps too late for benefit from intensive therapy.…”
Section: E Implications Of Severity Assessmentmentioning
confidence: 99%